The need for an educational comic on science laboratory safety - Nur Farha Shaafi; Mohammad Mubarrak Mohd Yusof; Ika Maryani (Intelektual Pustaka Media Utama, 2026)
In the study of design and development, one of the vital stages that need to be carried out is the needs analysis. In this study, a needs analysis is carried out to ensure that the educational comic produced is suitable for the users’ needs. This quantitative survey study was carried out to see the need for the development of the science laboratory educational comic on improving science laboratory safety awareness among secondary school students as well as to see students’ awareness and knowledge towards science laboratory safety. A set of needs analysis questionnaires was given to 131 secondary school students throughout Malaysia. The data obtained were analyzed descriptively, such as frequencies and percentages using Statistical Package for the Social Sciences (SPSS) version 23.0. The results of the analysis show that most respondents agree that this module is suitable for science laboratory safety awareness. A moderate level of average mean score of 3.53 also indicates that the level of awareness of regulations in the laboratory among average students is still low and needs to be improved. A high average mean score of 3.90 of respondents agreed that the development of science laboratory safety educational comic should be developed to improve science laboratory safety awareness among secondary school students. Most respondents agreed that emphasis should be placed on content and technical approaches in educational comics to develop a science laboratory safety educational comic that suits the needs of students, with a high average mean score of 3.73. The results of this study provide a brief overview of the need for a science laboratory educational comic on improving science laboratory safety awareness among secondary school students.